On the Criticism of Takano Yotaro's 'Japanese Collectivism' as an illusion - Alireza Rezaee (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It has been long believed that the Japanese are typical collectivists whereas Americans are typical individualists. To examine the validity of this common view, Takano reviewed empirical studies that compared Japanese and Americans and found that the overwhelming majority of those studies had not supported the common view. Takano examined whether the common view that Japanese are more collectivistic than Americans is valid or not in line with such these respects. He pointed out that those empirical studies that were directly related to the commonly accepted definition of individualism and collectivism did not support the common view and that those studies whose relations to individualism and collectivism were merely inferred were inappropriate in judging its validity. Also, he showed that the reference-group effect cannot entirely explain the past questionnaire studies failure to support the common view. In the current paper, the focus is on the meaning of “collectivism“, and it discusses the additional aspects of individualism/collectivism. This paper also focuses on the collectivism in Japanese business culture. The business culture in Japan stresses teamwork or collectivism, which ranks in stark contrast to the sense of individualism that stems from individual liberty and freedom espoused by western culture. Japanese culture places high importance on teamwork based on their philosophy of “wa”, or group harmony that holds the value of the greater good, as more important than valuing individual needs.